2012
DOI: 10.3109/03639045.2012.676048
|View full text |Cite
|
Sign up to set email alerts
|

Continuous production of drug nanoparticle suspensions via wet stirred media milling: a fresh look at the Rehbinder effect

Abstract: Nanoparticles of BCS Class II drugs are produced in wet stirred media mills operating in batch or recirculation mode with the goal of resolving the poor water-solubility issue. Scant information is available regarding the continuous production of drug nanoparticles via wet media milling. Griseofulvin and Naproxen were milled in both recirculation mode and multi-pass continuous mode to study the breakage dynamics and to determine the effects of suspension flow rate. The evolution of the median particle size was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 57 publications
5
51
0
Order By: Relevance
“…Comparative analysis of these thermograms to that of the as-received GF with T m =220°C and ΔH m =91.2 J/g suggests that the reduced ΔH m and T m upon milling could be mostly attributed to the dilution and encapsulation of the drug particles by the amorphous polymer (HPC). This finding accords very well with previous work (27) on the wet stirred media milling of GF, which showed identical DSC thermograms for the milled GF without stabilizers and the as-received GF. Overall, both the PXRD and DSC results here suggest that although vibratory media milling might have caused some defect formation in GF crystals, the crystalline nature of GF was largely preserved.…”
Section: Further Characterization Of the Gf Particlessupporting
confidence: 82%
See 3 more Smart Citations
“…Comparative analysis of these thermograms to that of the as-received GF with T m =220°C and ΔH m =91.2 J/g suggests that the reduced ΔH m and T m upon milling could be mostly attributed to the dilution and encapsulation of the drug particles by the amorphous polymer (HPC). This finding accords very well with previous work (27) on the wet stirred media milling of GF, which showed identical DSC thermograms for the milled GF without stabilizers and the as-received GF. Overall, both the PXRD and DSC results here suggest that although vibratory media milling might have caused some defect formation in GF crystals, the crystalline nature of GF was largely preserved.…”
Section: Further Characterization Of the Gf Particlessupporting
confidence: 82%
“…Overall, both the PXRD and DSC results here suggest that although vibratory media milling might have caused some defect formation in GF crystals, the crystalline nature of GF was largely preserved. This finding is not surprising because comprehensive characterization of the milled GF particles via DSC, XRD, and Raman spectroscopy demonstrated that even apparently more aggressive wet stirred media milling process did not cause notable change to the crystallinity (27,44). Moreover, similar observations were made for the crystallinity of other wet media milled, poorly water-soluble drugs such as fenofibrate (49)(50)(51) and indomethacin (44).…”
Section: Further Characterization Of the Gf Particlessupporting
confidence: 63%
See 2 more Smart Citations
“…The suspension produced from WSMM exhibited a median particle size of 0.144 μm while the suspensions made using as-received GF exhibited a median particle size of 5.031 μm. Extensive characterization of the dried GF nanosuspensions and GF-loaded films via DSC, PXRD, and Raman spectroscopy suggested that the crystalline nature of GF was largely preserved after wet milling (42) and incorporation into films including subsequent drying (36). Figure 4 shows SEM images for the cross-section of strip-films.…”
Section: Resultsmentioning
confidence: 99%